Increasing Tanker Truck Crew (AMT) Awareness of Occupational Safety and Health at Pertamina Using E-Booklet Media (Case Study Pertamina Fuel Terminal Boyolali) - Dawam Fahriza; Dani Fitria Brilianti; Frans Tohom (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Occupational Safety and Health (OHS) is a crucial aspect in fuel distribution operations, especially for Tanker Crews (AMT) as the frontline. This study aims to analyze the level of AMT awareness of OHS, identify inhibiting factors, and develop and measure the effectiveness of e-booklet media as a means of increasing OHS awareness in the Pertamina Fuel Terminal Boyolali environment. The research method used is mixed methods, with a quantitative approach through pre-test and post-test and a qualitative approach through interviews and observations. The research sample of 79 AMT was selected using a purposive sampling technique. The results showed that the level of AMT OHS awareness increased significantly after the e-booklet was provided. Internal factors such as knowledge and attitudes, as well as external factors such as supervision and the work environment, also influenced the level of awareness. The e-booklet media proved effective as a practical, interactive, and easily accessible educational medium, thus recommended as a means of continuous OHS training. This research contributes to the development of digital media-based occupational safety strategies in the hazardous materials transportation sector.